Force-velocity muscular profiles and jumping performances of soccer goalkeeper - Hervéou, T.; Rahmani, A.; Chorin, F.; Frère, J.; Ripamonti, M.; Durand, S. (Science & Sports, 2018)
Aims: The aim of the study was to assess mechanical muscle capacities and profiles of well-trained soccer goalkeepers playing at a national amateur level. Methods: Eleven goalkeepers (from 4th French division) performed vertical jump tests and series of loaded half squat and bench throw tests to assess lower and upper limbs force-velocity profiles, respectively. Force, velocity and power produced during each exercise were determined using a guided barbell. Maximal theoretical velocity and maximal theoretical force were determined from the force-velocity profiles. Slopes of those profiles were also calculated. Results: Vertical jump performances were 38.5±4.5cm for the squat jump and 41.6±5.5cm for the countermovement jump. Lower limbs stiffness was 304.2±55.1N.m-1.kg-1. Lower limbs force-velocity profile was described by a slope of -11.5±4.0N.s.m-1.kg-1, with maximal theoretical force and velocity reaching 34.3±5.9N.kg-1 and 3.2±0.2m.s-1, respectively. Upper limbs muscular profile was described by a slope of -3.7±1.1N.s.m-1.kg-1, with maximal theoretical force and velocity of 13.6±3.7N.kg-1 and 3.7±0.6m.s-1, respectively. These values reveal that goalkeepers` muscles profiles are oriented towards velocity. Conclusion: This suggests that whatever the goalkeepers` level, specific and conditioning trainings should mainly focus on velocity to optimize the performance of this specific soccer player.